Students Flock to Game Design. (Communications of the ACM, 2009)
The article reports that game design has become a popular major at colleges and universities in the U.S. Governments and universities are developing strategies to reverse the downturn in computer science students, the article states. Other topics include game creation which crosses several disciplines, game companies which recruit many people to work in studios, and blockbuster games that require the efforts of more than 100 developers. Also discussed is the creation of digital scenes and the composition of music.